Surgery decision conflict and its related factors among newly diagnosed early breast cancer patients in China: A cross‐sectional study - Han Tang; Shang Wang; Shiqi Dong; Ruofei Du; Xiao Yang; Panpan Cui; Wei Liu; Jie Kou; Changying Chen (Wiley, 2021)
Abstract Aim The aim of this study was to explore surgery decision conflict and its related factors among newly diagnosed early breast cancer patients in China. Design A cross‐sectional survey study was conducted. Methods A total of 262 patients confronted with surgery decision‐making were enrolled. The related factors were assessed with a demographic questionnaire, the Chinese version of the Decision Conflict Scale (DCS‐C‐16) and the Patient Participation Competence Scale (PPCS). Results Patients had a high level of decision conflict that was negatively correlated with the PPCS score. Age, marital status, living environment, education level, family income, cancer stage and the PPCS score were independent factors influencing decision conflict. Marital status, education level, cancer stage and participation competence were significant predictors of decision conflict. Patients who had higher participation competence were married, were well educated and had a lower cancer stage were likely to experience lower decision conflict.